FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELANCARAN ASI PADA IBU MENYUSUI 0-3 BULAN DI DESA PANDARUNGAN BANYUWANGI - Novitasari, Erlin; Mashouro, Yeni (Ensiklopedia of Journal, 2025)
Exclusive breastfeeding is the provision of breast milk for the first 6 months of a baby's life without any additional food. The success of exclusive breastfeeding is influenced by several factors, such as perception, breastmilk fluency, knowledge, and maternal nutritional intake. This study aims to analyze the relationship between age, parity, and education of breastfeeding mothers with breastmilk fluency. The study used a cross-sectional approach with a total sampling technique so that a sample of 30 respondents of breastfeeding mothers aged 0-3 months was obtained. The study was conducted in November-December 2023. The research instrument used a questionnaire about the characteristics of respondents and 9 indicators of breastmilk fluency. The research analysis used chi square and all respondents had signed an informed consent. The results of the study showed that there was a correlation p between age and parity with breastmilk fluency with a p value of 0.026 each, and there was no correlation between education and breastmilk fluency. Based on the results of the study, it is recommended that midwives can provide education during pregnancy regarding several factors that can affect breastmilk fluency so that the coverage of exclusive breastfeeding can increase..Keywords: Factors, Age, education, parity, breastmilk fluency